2003
DOI: 10.1177/152660280301000612
|View full text |Cite
|
Sign up to set email alerts
|

Non-Axisymmetrical (Life-Like) Abdominal Aortic Aneurysm Models: A Do-It-Yourself Approach

Abstract: Chemical metal can be manipulated quite easily to make a mould of any required size or surface character, which then allows the manufacture of a well-matched latex model for biophysical studies of non-axisymmetrical abdominal aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The latex has a Young's modulus ðEÞ of 5.151872 N/mm 2 , measured by a Hounsfield tensometer. A solution of glycerol in water (55:45 v/v, r ¼ 1172 kg=m 3 ; viscosity ¼ 15.53 cP at 25 8C) was used as a blood analogue. The increased density was calculated to generate the high-pressure setting within the limitations of the solenoid angle seat valve.…”
Section: Methodsmentioning
confidence: 99%
“…The latex has a Young's modulus ðEÞ of 5.151872 N/mm 2 , measured by a Hounsfield tensometer. A solution of glycerol in water (55:45 v/v, r ¼ 1172 kg=m 3 ; viscosity ¼ 15.53 cP at 25 8C) was used as a blood analogue. The increased density was calculated to generate the high-pressure setting within the limitations of the solenoid angle seat valve.…”
Section: Methodsmentioning
confidence: 99%
“…2 The human thrombus that is obtained during open aneurysm surgery cannot be fitted exactly in aneurysm models. Pre-stress is induced by curvature of the graft due to patient anatomy.…”
Section: Replymentioning
confidence: 99%
“…Using air that quite effectively replicates the pressures within an axially symmetric container may be an oversimplification that may not sufficiently mimic the intrasac environment. This could have been done using real or simulated thrombus within a more realistic AAA model 2,3 ; this is particularly so given that their own results previously have shown that thrombus may contribute to inconsistencies in the readings. 4 It may be that thrombus actually has a damping effect on sensor movement!…”
mentioning
confidence: 99%
“…Because of this, the compliance (or stiffness) of arteries has become the attribute which researchers attempt to mimic [10,16]. The manufacturing methods for creating both idealised and realistic AAA models have been previously reported [10,1621]. O’ Brien et al [19] and Doyle et al [20] have verified a lost wax manufacturing technique and reported that the variation in wall thickness for large vessel models manufactured using this technique was between 4–11%.…”
Section: Introductionmentioning
confidence: 99%